Social media and digital marketing strategies for combating stunting: An intervention in Sidomulyo Village, Secang - Eko Muh Widodo; Anindita Wahyu Astari; Yulia Larasati; Awaludin Yusuf Basuki; Rosyid Mubarak; Andika Muhammad Rafi (Universitas Muhammadiyah Magelang, 2024)
Business actors increasingly need to master technology to expand their market reach. However, many MSMEs in Sidomulyo Village have not adopted digital platforms for marketing and sales. This initiative introduced digital marketing and the use of social media to these business actors. Through socialization, counseling, and mentoring, participants gained knowledge about online sales platforms, mastered online marketing techniques, and successfully launched online product promotions. Additionally, the project facilitated the creation of new Cendana batik designs, improved product packaging, and enhanced product photography skills.